"Give Us a Chance": Understanding Job Seeking Among Women Experiencing Homelessness. Issue 3 (September 2017) - Groton, Danielle B.; Gromer, Jill M.; Mennicke, Annelise M.; Lee, Jungup; Gul, Mehnaz; Dupree, Erin M.; Munn, Jean
Abstract : The purpose of this phenomenological study was to explore perceptions of job seeking from women experiencing homelessness. Participants ( N = 9) were interviewed at a transitional housing facility in North Florida. Thematic analysis found several manifest and latent themes related to stigma, barriers, and perseverance. The findings of this study support the existing literature on the management of social stigma by people experiencing homelessness. It also provides new findings that allow for a more nuanced understanding of the factors identified by experts in the job‐seeking experiences of women who are homeless.